PERCEPATAN PENGEMBANGAN INOVASI TEKNOLOGI PTT JAGUNG PADA BERBAGAI AGROEKOSISTEM PEMBANGUNAN PERTANIAN ACCELERATION DEVELOPMENT OF CORN ICM TECHNOLOGY INNOVATION AT SEVERAL AGROECOSYSTEM AGRICULTURE DEVELOPMENT - M.P Sirappa; Daniel Pasambe (Agros Journal of Agriculture Science, 2014)
Inovasi teknologi pengelolaan tanaman terpadu jagung mengintegrasikan berbagai komponen teknologi secara sinergis untuk memecahkan masalah setempat, meningkatkan efisiensi penggunaan input, memelihara dan meningkatkan kesuburan tanah. Balitbangtan merakit varietas unggul palawija, genjah, tahan hama penyakit, toleran lingkungan, dan hasil sesuai preferensi konsumen. Varietas unggul baru yang disarankan untuk  agroekosistem lahan sawah tadah hujan: Lamuru, Srikandi Kuning-1, Srikandi Putih-1, Bima-1, Semar-10; Untuk lahan kering beriklim basah: Bisma, Lamuru, Srikandi Kuning-1, Srikandi  Putih-1, Bima-1, Semar-10; Untuk lahan kering masam beriklim basah: Sukmaraga; untuk lahan kering beriklim kering: Lamuru, Srikandi Kuning-1, Srikandi Putih-1. Untuk pakan ternak: Bisma, Lamuru, Bima-1, Semar-10, untuk bahan pangan: Srikandi Kuning-1, Srikandi Putih-1. Strategi pengembangan jagung: melalui survei atau PRA, verifikasi dan evaluasi teknologi produksi, temu lapang, sosialisasi teknologi produksi, dan pembinaan penangkar benih.Technology innovation of corn integrated crop management (ICM) is formed of concept with integrated a variety of technology component which synergy interdependent so disperse local problem, increasing eficiency input, take care of and increasingsoil fertility. Agriculture Agency of Research Development agitating for assemble new superior varieties which have a highest production, early ripening, resistent main pest and disease, tolerance of marginal domain, and yield quality which accord with consumer preference.  A new superior variety which admissible for agroecosystem rain field are Lamuru, Srikandi Kuning-1, Srikandi Putih-1, Bima-1, dan Semar-10; For dry land wet climate are Bisma, Lamuru, Srikandi Kuning-1, Srikandi Putih-1, Bima-1 and Semar-10; For acid dry land wet climate are Sukmaraga; and for dry land and dry climate are Lamuru, Srikandi Kuning-1 and Srikandi Putih-1. For necessity silage, development directed towards varieties of Bisma, Lamuru, Bima-1, and Semar-10, whereas for food matter are Srikandi Kuning-1 and Srikandi Putih-1. Several strategy for accelerate of corn development, especially varieties which producting by Agriculture Agency of Research Development for farmer are trough survey or PRA, verification and evaluation technology production, field encountered, socialization of technology production, and management of seed measuring.